2023
DOI: 10.1039/d3nj01384g
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–poly(vinyl alcohol)–ionic liquid-grafted hydrogel for treating wastewater

Abstract: Herein, a chitosan–poly(vinyl alcohol)–ionic liquid-grafted hydrogel was prepared for water purification. The hydrogel was characterized using various techniques, including nuclear magnetic resonance spectroscopy, X-ray photoelectron spectroscopy, infrared spectroscopy, powder X-ray...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…S21B †). Moreover, a leaching study 41,42 was conducted to assess the stability of IL@MWCNTs after Hg 2+ adsorption. A quantity of 20 mg of IL@MWCNTs adsorbed with Hg 2+ was suspended in varying pH solutions for 12 h. The suspension was separated by filtration, and the leached amount of mercury in the supernatant was analysed by atomic adsorption spectrometry (AAS) (Fig.…”
Section: Development Of the Organic Cation (Il)-modified Mwcnts And I...mentioning
confidence: 99%
“…S21B †). Moreover, a leaching study 41,42 was conducted to assess the stability of IL@MWCNTs after Hg 2+ adsorption. A quantity of 20 mg of IL@MWCNTs adsorbed with Hg 2+ was suspended in varying pH solutions for 12 h. The suspension was separated by filtration, and the leached amount of mercury in the supernatant was analysed by atomic adsorption spectrometry (AAS) (Fig.…”
Section: Development Of the Organic Cation (Il)-modified Mwcnts And I...mentioning
confidence: 99%
“…The incorporation of nanoparticles in the polymer matrix has a significant influence on the membrane characteristics as formed during the polymer phase separation. The trade-off between permeability and selectivity of polymeric membranes is solved by incorporating these nanoparticles, thus altering the characteristics of the membrane’s top layer, pore size, thickness, hydrophilicity, charge potential, and parameters related to the membrane structure such as the porosity and macro-void morphology of the asymmetric support. , Thus, PES and the PES@R1.Co 2+ hybrid membrane have been synthesized using a nonsolvent-induced phase inversion technique that has been characterized using FTIR spectroscopy. The chemical structure of PES contains benzene, ether, and sulfone moieties.…”
Section: Application Of the Developed R1co2+ Self-assembled Materialsmentioning
confidence: 99%
“…The development of porous materials with special wetting properties used as filters or sorbents is a topic of continuously growing interest, giving a great promise in tackling these problems. , In particular, hydrogels are one of the top emerging materials with such favorable interfacial features for applications in the water sector. , Both the wetting properties and their ability to absorb large amounts of water make them attractive for integrated water purification applications. Nevertheless, only a few studies have been reported so far on multifunctional hydrogels that are able to efficiently and simultaneously purify water from oil and water-soluble pollutants. Thus, the development of a simple, single-step, and energy-efficient purification method for oily wastewaters containing different water-soluble contaminants is of great importance.…”
Section: Introductionmentioning
confidence: 99%